Financial Literacy as a Mediator of Gen Z’s Financial Management Behavior - Johny Budiman; Vivien Vivien (Jurnal Akuntansi, Keuangan, dan Manajemen, 2026)
Purpose: This study examines the relationships between financial attitudes, socialization, experience, and knowledge and financial management behavior, with a specific focus on the mediating role of financial literacy among Generation Z in Batam City. Methodology/approach: This study used a quantitative approach in Batam, Indonesia. Data were collected from 394 Generation Z respondents using a structured questionnaire adapted from prior research. The analysis was performed using PLS-SEM with the SmartPLS 3.0 software. Results/findings: The findings show that financial socialization and experience significantly improve financial literacy, whereas attitudes and knowledge have little effect. Financial literacy directly influences financial management behavior and mediates the impact of socialization and experience, but not attitudes, highlighting its key role in shaping Generation Z’s financial behavior Conclusions: The analysis confirmed that all variables met the validity and reliability standards. Socialization and experience significantly influenced financial literacy, whereas attitude and knowledge had minimal effects. It also directly affected financial management behavior and mediated the impact of socialization and experience, but not attitude. Limitations: This study focused only on respondents from Batam and used quantitative methods. This study also did not consider other factors that may affect individual financial management and did not explore the mediating role of financial literacy in depth. Contributions: This study offers insights into financial education by showing how practical experience and social interaction can enhance Generation Z’s financial literacy and guide the design of effective educational programs.